The development of a generic just-in-time supply chain optimisation software tool - Bredenkamp, F.v.B. (Stellenbosch : University of Stellenbosch, 2008)
The demand from modern day customers for quality products, supplied in any quantity and within a short lead-time, forces organisations to stock the correct amount of inventory in the correct locations in its supply chain. Establishing the correct inventory levels within an organisation’s supply chain is complicated by the various stochastic processes occurring in a supply chain. The thesis is aimed at the development of a generic Just-In-Time (JIT) supply chain optimisation software tool, whereby the correct inventory levels for an organisation can be determined. These inventory levels will ensure that the organisation will achieve a predefined customer service level at the minimum cost to the company. The tool was developed and satisfactory results were obtained using the Harmony Search Algorithm (HSA) for optimising the inventory levels.